Prototype Development for the Treatment of Periprosthetic Fractures of the Distal Femur - Muizelaar, Aaron (My University, 2012)
Current stabilization methods for periprosthetic fractures of the distal femur have been inadequate in achieving sufficient fixation and can lead to complications rates as high as 29%. Therefore, the overall objective of this study was to design, manufacture and evaluate (experimentally and computationally) a novel plating method for improving the treatment of periprosthetic fractures of the distal femur.
Medial and lateral prototype plates were designed and manufactured based on the geometry of a synthetic femur and a femoral prosthesis. The two plates were linked via a compression screw and a small tab on each plate that inserts into pre-existing slots on the prosthesis to enhance rigidity of the construct. Synthetic femurs were used to assess the ability of the prototype plates to stabilize a periprosthetic fracture compared to a traditional single lateral plate. Each femur was subjected to a testing protocol that involved compressive and bending loading of the sample. The relative motion between the distal and proximal fragments during loading was then measured using both 2D and 3D motion tracking techniques. Both techniques revealed that the prototype bilateral plates were able to reduce motion of the fracture site compared to a single lateral plate.
The final objective concerned the development of a finite element model to represent the experimental testing. The fracture gap motion obtained from the final model did not completely agree with the experimental data; however, additional experimental measurements found that the majority of these differences could be attributed to simplification made at the tab-slot interaction. Despite the difference, the model represents a significant step forward in the simulation of periprosthetic fracture treatment, and further refinement would allow for optimization of the plate design.
Overall, the results of this thesis indicate that an alternative approach to treating periprosthetic fractures exists that is capable of improving fracture stabilization.
Keywords: periprosthetic fracture; distal femur; bilateral fracture fixation plates; biomechanics; biomechanical testing; finite element analysis; Biomedical devices and instrumentation; Biomedical devices and instrumentation